2014
DOI: 10.4161/hv.34313
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions that apply new media to improve vaccine uptake and vaccine coverage

Abstract: Background: Vaccine-preventable diseases (VPD) are still a major cause of morbidity and mortality worldwide. In high and middle-income settings, immunization coverage is relatively high. However, in many countries coverage rates of routinely recommended vaccines are still below the targets established by international and national advisory committees. Progress in the field of communication technology might provide useful tools to enhance immunization strategies.Objective: To systematically collect and summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
121
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(133 citation statements)
references
References 31 publications
(142 reference statements)
7
121
0
1
Order By: Relevance
“…For instance, Odone et al reviewed interventions that apply new media (Internet and social media) to promote vaccine uptake and increase vaccination coverage [16]. These authors concluded that text messaging, accessing vaccination campaign websites, using patient-held web-based portals and computerised reminders may increase vaccine uptake, whereas there was insufficient evidence to determine effectiveness of use of social networks, email communication and smartphone applications [17]. Cairns et al examined the effectiveness of promotional communications in the European context and also concluded that there is good evidence that a range of promotional communications can positively change knowledge, attitudes and behaviours.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Odone et al reviewed interventions that apply new media (Internet and social media) to promote vaccine uptake and increase vaccination coverage [16]. These authors concluded that text messaging, accessing vaccination campaign websites, using patient-held web-based portals and computerised reminders may increase vaccine uptake, whereas there was insufficient evidence to determine effectiveness of use of social networks, email communication and smartphone applications [17]. Cairns et al examined the effectiveness of promotional communications in the European context and also concluded that there is good evidence that a range of promotional communications can positively change knowledge, attitudes and behaviours.…”
Section: Resultsmentioning
confidence: 97%
“…Globally, most of the interventions analysed in the reviews that were examined for the present study were primarily to inform or to educate about vaccination [13,14,16,17,20,21,25]. Brief written educational interventions (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These achievements demand urgent attention to the social equity for both genders in healthcare (84); advocating and educating the general public and the medical community on HPV vaccination is a top priority (85).…”
Section: Resultsmentioning
confidence: 99%
“…The growing role of Information and Communication Technologies (ICT) and 'new media' should be leveraged by institutions and the public health community to increase vaccine uptake and ultimately immunization coverage rates. 18 Innovative tools of proven effectiveness, which need to be widely implemented, include: immunization information systems, computerized reminders for providers and electronic remind/recall systems for parents and patients; 11. Efforts should be devoted to the development of wider partnerships between the stakeholders involved in the various phases of the immunization process, of enhanced joint efforts and of strengthened cross-program links between health services; 12.…”
mentioning
confidence: 99%